The reaction of teachers to external evaluations of schools: Proposition of a Model - Durán, Diego (Education Policy Analysis Archives, 2004)
During the decade of the 1990s, several changes took place in education focusing on evaluating the academic achievements of students in their schools. Many of those assessments sought to reveal the "real" situation of the schools and their quality, in most of the cases limited to the academic performance of the students. Some of these assessments also sought to influence the organization of the schools. This article will discuss how the goal of regulating the system has not always been achieved. On the contrary, most of the time, one can discern an increasing resistance among the main actors of the system (especially teachers) toward the politics of regulating schools through the use of assessment instruments. I present a model that allows a closer view of this conflict based on teachers' perceptions of these assessments and the educational project of their schools.